The development and validation of an integrated assessment of irrational beliefs concerning basic psychological needs: the rational emotive self-determination scale for workers - Murat Artiran; Pinar Tinaz; Ömer Faruk Simsek; Anthony Miller; Katia Correa Vione; Martin James Turner (Frontiers in Psychiatry)
IntroductionRecently a new approach to understanding human behaviour has emerged that integrates rational emotive behaviour therapy (REBT) from the cognitive behavioural tradition, and self-determination theory (SDT) from the humanistic tradition. In the current study, we develop a psychometric that conceptualizes this new approach in organisational settings; the rational emotive self-determination scale for work (RESD-W). The RESD-W assesses respondents’ irrational beliefs (from REBT) concerning the basic psychological needs (from SDT), namely perceptions of autonomy, competence, and relatedness within their work life. The RESD-W builds on initial validations of the RESD in adolescent populations (RESD-A).MethodsIn the current paper, the psychometric properties of the 16-item RESD-W were examined across five studies, in which the factor structure, the reliability of the scale, and construct and criterion-oriented validity of the RESD-W were assessed.ResultsAnalyses confirmed theoretical expectations and yielded good psychometric properties. Scores in the RESD-W were associated with anxiety and depression, and negative emotions in the workplace.DiscussionThe results are discussed regarding practice, highlighting that work related psychological wellbeing may be predicated on the integration of irrational beliefs and basic psychological needs.